Assessment of the performance and competitiveness of the selected clusters in the Moravian-Silesian Region - Hana Stverkova; Vlasta Humlova (Institute of Economic Research (IER), 2015)
In recent years have been recording the number of sectorial clusters of firms and their links with a research and academic sphere unprecedented prosperity in the Czech Republic. The trend and popularity of clusters in regions are considered as an important source of competitive advantage of given locality. In particular SMEs can in this way overcome a certain weaknesses of this type of business and strategically use of so-called synergistic effect. Many times, it was stressed to be SMEs as the foundation of any economy, but they do not have the necessary economic force. These problems help to remove specific form alliances - the cluster. The competitiveness of regions goes hand in hand with support for cluster organizations. Clusters are perceived as modern and well-defined type groupings of entities from certain industry or field. The aim of this paper is to evaluate and assess the efficiency and competitiveness of selected cluster groups in the Moravian and Silesian region. The partial aim is a generalization of international methodologies for assessing the performance of clusters and linking this methodology with the basic principles of competitiveness evaluation. On practical example will be applied Porter's diamond combined with the EFQM model and Cluster Management Excellence methodology. The outcome of the paper will be the evaluation of cluster initiatives. There will also be proposed basic precautions that should lead to the desired performance level of international excellence cluster. For the selection of appropriate proposals will be used the multi-criteria decision analysis, to identify those measures that are currently most advantageous for the cluster.
Keywords: M1; M14; M21; L62; F6; R10; 330; cluster; competitiveness; performance; BEE model; Moravian-Silesian Region